An Industrial systems design study on RICAD Trading - Dayco, Jose Roberto D. (College of Engineering, 2004)
RICAD is in the business of retailing architectural related materials like laminates and tiles since 1999. Initial analysis reveals little structure in its organization. From interviews and surveys taken from personnel and related factors from the industry concrete ideas and targets are set forth for the company in order to evaluate its performance through the years and to set the direction for the company. The company's processes are defined and tabulated for availability should process change be a consideration. The entire system was documented for accessibility for further improvement and analysis. Later in the study, the industry and the market was analysed to maximize the environmental position. The group evaluated its strengths, weaknesses, opportunities and threats to isolate areas wherein the study shall give results that have the greatest impact for the company's improvement. This step showed that targets, capacity and performance along with a new service provides the greatest potential for overall improvement. Targets were set using historic data along with industry analysis. Tracking Programs with key performance indicators were given to better appreciate the company's efforts. Capacity is focused at meeting demand, increasing availability and addressing a new market. As supplementary for decision analysis, financial ratios were calculated to better define the company's financial position. The study ends with implementation plans for proposed changes along with areas for further study.